Gestión de las cuentas por cobrar de la Comercializadora Agrícola JOFLOSA S.A. del cantón Montalvo en los períodos 2021 – 2022. - Ávila Toalombo, Allison Belén (2024)
The study on JOFLOSA S.A. examines accounts receivable management, highlighting the need for effective credit policies and sound financial management to foster liquidity and business growth. The objective of this study is to evaluate the accounts receivable management process of the Comercializadora Agrícola JOFLOSA S.A. of the Montalvo canton in the periods 2021 - 2022. This work is closely related to the Financial, Administrative, Tax, Audit and Control Management research line, along with the “Audit and Control” research subline. Through a mixed methodological approach combining financial analysis and an interview, a notable increase in credit sales and an increase in accounts receivable was identified, evidencing challenges in controlling credit risk and the absence of provisions for bad debts. The findings underline an ambitious expansion strategy, but also highlight the importance of adopting meticulous risk management to ensure the company's long-term financial stability and sustainability. This comprehensive analysis offers deep insight into the financial practices of JOFLOSA S.A., emphasizing the relevance of balancing growth with prudent financial risk management.